2015
DOI: 10.1089/ars.2013.5743
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized High-Density Lipoprotein Impairs Endothelial Progenitor Cells' Function by Activation of CD36-MAPK-TSP-1 Pathways

Abstract: Activation of CD36-p38 MAPK-TSP-1 pathways contributes to the pathological effects of ox-HDL on EPCs' dysfunction, which might be one of the potential etiological factors responsible for the disturbed neovascularization in chronic ischemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 75 publications
(81 reference statements)
0
23
0
Order By: Relevance
“…Probucol prevents LDL oxidation [85,86], increases SOD level and activity [87], decreases the levels of ox-LDL and CRP [72]. Probucol has been reported to rescue cigarette smoke-induced impairment of ischemiainduced neovascularization by improving the function of EPCs [48], and protect EPCs from oxidized high-density lipoprotein (ox-HDL) [49]. Additionally, it has been reported that probucol is able to prevent ROS-induced inactivation of endothelium-derived NO [88], reduce endogenous NO synthase inhibitor [43], and increase the level and function of NO, which could regulate the self-renewal, viability, migration, proliferation, and differentiation of EPCs [89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probucol prevents LDL oxidation [85,86], increases SOD level and activity [87], decreases the levels of ox-LDL and CRP [72]. Probucol has been reported to rescue cigarette smoke-induced impairment of ischemiainduced neovascularization by improving the function of EPCs [48], and protect EPCs from oxidized high-density lipoprotein (ox-HDL) [49]. Additionally, it has been reported that probucol is able to prevent ROS-induced inactivation of endothelium-derived NO [88], reduce endogenous NO synthase inhibitor [43], and increase the level and function of NO, which could regulate the self-renewal, viability, migration, proliferation, and differentiation of EPCs [89].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired ischemia-induced neovascularization by cigarette smoke could also be rescued by probucol via improved function of EPCs [48]. Probucol treatment could also protect EPCs from oxidized high-density lipoprotein (ox-HDL)-induced apoptosis [49]. The present study aimed to determine whether probucol could have protective effects on circulating MNCs and EPCs in mouse treated with ox-LDL and in hyperlipidemic patients with elevated ox-LDL level.…”
Section: Introductionmentioning
confidence: 95%
“…Angiogenetic activity of CD36 in endothelial cells is a result of its ability to activate specific cascade signal caused by proangiogenetic response directed to apoptotic response. 3,54,55 Muscle cells CD36 receptor is 85% homology with FAT/CD36 protein -fatty acid translocase. Its main role is cellular transportation of longchain fatty acids.…”
Section: Plateletsmentioning
confidence: 99%
“…However, the effect of peptides on TNF-and phorbol ester-induced inflammatory stimulation in various cells, including macrophages, was only marginally affected by SAHPs (54). Furthermore, recent data suggest that CD36 is one of the most important receptors associated with bacterial uptake, bacterial endotoxic cellular cytotoxicity (28), and acute and chronic kidney injury (28,(55)(56)(57). These recent data suggest that the vicious cycles of pathogen associated molecular pattern-induced inflammation and DAMP-induced tissue damage may well be mediated through CD36 (58,59).…”
Section: Discussionmentioning
confidence: 97%